Ikan Nyalian (Barbodes binotatus Valenciennes, 1842) di Danau Tamblingan, Buleleng, Bali Dilihat dari Aspek Makanannya - Pramana, Made Arya Surya; Pertami, Nyoman Dati; Pebriani, Dewa Ayu Angga (Journal of Marine and Aquatic Sciences; Vol 9 No 2 (2023)DO - 10.24843/jmas.2023.v09.i02.p10, 2024)
Tamblingan Lake is one of four lakes in Bali which is located in Munduk Village, Banjar District, Buleleng Regency, Bali. Spotted barb (Barbodes binotatus) is a freshwater fish belonging to the Cyprinidae  family found in Tamblingan Lake. Information regarding the food composition of spotted barb in Tamblingan Lake has not been carried out. This research aims to determine the food of nyalian fish by observing the composition of the type of food in the Tamblingan Lake Waters. Fish sampling was carried out in January-June 2019 using gill nets with a mesh size of 0.5; 1.0; 1.5; 2.0; 2.5; 3.0 cm with length of 300 m and height of 2 m. Fishing was carried out at five stations with different characteristics. Fish samples obtained during the research were 180 fish. The composition food of spotted barb consists of 37 types of organisms consisting of 6 classes of phytoplankton, 6 classes of zooplankton, 1 class of fungi and 1 class of aquatic plants. Most types of food organisms come from the Bacillariophyceae class, which is 16 genera. Species of Surirella sp ., Navicula sp., Cymbella sp., and Pinnularia sp. is a genus of the Bacillariophyceae class which is often found every month of observation with the frequency of occurrence respectively 174, 105, 126 and 112. There was not much difference in food composition between nyalian fish in each month of observation. Spotted barb include omnivorous fish (tend to be herbivores) and classified as euryfagus.